Pre-Mastectomy Breast Reconstruction Intentions in Women with Breast Cancer: Psychosocial and Personality Predictors Informing Mental Health Promotion - Valentini Bochtsou; Eleni I. Effraimidou; Maria Samakouri; Spyridon Plakias; Maria-Eleni Zachou; Aikaterini Arvaniti (Healthcare, 2025)
Background/Objectives: Despite the psychological benefits of breast reconstruction (BR) after mastectomy, uptake remains limited among women with breast cancer. This study explores psychosocial and personality predictors of BR intentions in the pre-mastectomy phase, aiming to inform strategies for mental health promotion in oncology care. Methods: This cross-sectional analysis used preoperative data from a longitudinal study at a university hospital in Greece. Women with primary breast cancer scheduled for mastectomy completed a battery of validated self-report measures, including the International Personality Item Big-Five Factor Markers (IPIP-BFFM), the Hospital Anxiety and Depression Scale (HADS), and the Short Form-36 Health Survey (SF-36). Demographic, clinical, and psychosocial data were also collected. Binary logistic regression was used to examine predictors of (a) BR information-seeking and (b) BR intention. Results: Seventy-four women participated (mean age = 61.1 years). Older age predicted lower BR intention (Exp(b) = 0.897, 95% CI: 0.829–0.970) and information-seeking (Exp(b) = 0.925, 95% CI: 0.859–0.997). Single/divorced status was associated with reduced BR information-seeking (Exp(b) = 0.053, 95% CI: 0.005–0.549). Openness to experience significantly predicted both outcomes (BR information-seeking: Exp(b) = 1.115, 95% CI: 1.028–1.209); BR intention: Exp(b) = 1.095, 95% CI: 1.016–1.181). Higher physical health-related QoL scores were associated with increased BR intention (Exp(b) = 1.039, 95% CI: 1.007–1.072), whereas higher mental health-related QoL (Exp(b) = 0.952, 95% CI: 0.912–0.994) and higher depression scores (Exp(b) = 0.797, 95% CI: 0.638–0.996) were linked to decreased BR intent. No psychological factor significantly predicted information-seeking. Conclusions: These findings underscore the value of psychosocial screening and personality-informed counseling prior to surgery. By identifying individuals less likely to seek information or consider BR, pre-mastectomy assessments can contribute to tailored, mental health-promoting interventions and support informed, patient-centered surgical decision-making.